The 9th International Conference "Environmental Engineering 2014" 2014
DOI: 10.3846/enviro.2014.162
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bitumen fractional composition depending on the crude oil type and production technology

Abstract: The present paper focuses on the analysis of the bitumen quality which can be a relevant issue in the performance of road surfacing. Using bitumen from different producers with the same physical characteristics can be significantly different in fractional composition. Crude oil selection and processing play an important role in bitumen properties. Changes in processing and crude sources even within a market may also lead to variability in bitumen fractional composition. The aim of this study is to determine to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 19 publications
0
27
0
2
Order By: Relevance
“…According to the European specification (EN 12597), bitumen is defined as a virtually involatile, adhesive, and waterproofing material derived from crude oil, or present in natural asphalt, which is completely or nearly completely soluble in toluene, and very viscous or nearly solid at ambient temperatures [1]. It is well-accepted that the original characteristics of bitumen are highly dependent on its production and processing procedure, as well as bitumen crude oil characteristics [2]. Good crude oils and proper distillation processes can enhance bitumen properties.…”
Section: Bitumen Functionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the European specification (EN 12597), bitumen is defined as a virtually involatile, adhesive, and waterproofing material derived from crude oil, or present in natural asphalt, which is completely or nearly completely soluble in toluene, and very viscous or nearly solid at ambient temperatures [1]. It is well-accepted that the original characteristics of bitumen are highly dependent on its production and processing procedure, as well as bitumen crude oil characteristics [2]. Good crude oils and proper distillation processes can enhance bitumen properties.…”
Section: Bitumen Functionalitymentioning
confidence: 99%
“…As the results have shown a considerable increase in the bitumen/polymer compatibility, it has been suggested that using ternary bitumen/polymer/clay (BPC) systems, the PmB's performances may be improved. In particular it has been claimed that the use of PLS in PmBs has mainly two effects: (1) improving the aging resistance of PmB with barrier properties of the dispersed clay platelets and (2) enhancing the storage stability of PmB by decreasing the density difference between polymer modifiers and bitumen [68].…”
mentioning
confidence: 99%
“…Moreover, comparing the SARA fraction results from TLC-FID performed in different laboratories is challenging due to the use of the differing solvents and times of elution (often not reported in literature) (Masson et al 2001;Higuerey et al 2002;Tabatabaee and Kurth 2017;Paliukaite et al 2014). The laboratories choose the method for the inside quality control of the product, or for the compari-son between the products in development stage, based on inside correlations (Lehto 1988;Teugels and Zwijsen 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The colloidal stability decreases with the increase in the colloidal index and becomes unstable if the index value is from 0.5 to 2.7 ( 26 ).…”
Section: Materials and Test Methodsmentioning
confidence: 99%